Dynamics of Battered Filipino Women: Validating a Dynamics of Abuse Model - Estrellado, Alicia F.; Salazar-Clemeña , Rose Marie (Silliman Journal, 2022)
This study was designed to validate Estrellado and SalazarClemeña’s (2007) Dynamics of Abuse Model. It also aimed to further explore and analyze dynamics of Filipino battered women. "RVBMJUBUJWFTUVEZPGCBUUFSFEXPNFOXBTDPOEVDUFEVTJOHJO depth interview. Participants reported 19 categories of abuse, 20 categories of contributing factors to abuse, 16 categories of effects of abuse on women’s perception of self, view of the world, sense of well-being, and interpersonal relationships, and 13 categories of coping strategies. Responses were coded based on Estrellado and Salazar-Clemeña’s model. The study demonstrated that Dynamics of Abuse Model can be useful as a conceptual framework for understanding concerns of battered women. Implications for counseling practice and research are discussed.